Prevalence and factors associated with uncontrolled blood pressure in dialysis patients using antihypertensive: a narrative review - Pulungan, Yulianasari; Nugroho, Agung Endro; Pramantara, I Dewa Putu (Indonesian Journal of Pharmacology and Therapy, 2023)
Hypertension in patients with end-stage chronic kidney disease undergoing hemodialysis is difficult to control leading to a significant risk factor for a cardiovascular event. The aimed of this review is to summarize the prevalence of uncontrolled blood pressure in dialysis patients. This review hopefully can serve as a valuable reference and source of insight for clinicians in their efforts to attain controlled blood pressure in dialysis patients. The relevant literatures was undertaken from PubMed, Scopus, and Google Scholar for studies addressing the factor associated with uncontrolled blood pressure in hemodialysis patients using antihypertensives from 2013 to 2023. Combinations of search terms were "uncontrolled" and "blood pressure" and "dialysis" and "antihypertensive”. Any study in English, including randomized control trials, cohort, case-control, and cross-sectional studies was included. Uncontrolled blood pressure is very common among hypertension in dialysis patients (28.7 - 78.33% of cases). Factors affecting blood pressure in dialysis patients include age, obesity, and comorbidity (diabetes and stage of chronic kidney disease). Although the relationship between gender, the number of antihypertensive, the number of dialysis, and the length of dialysis sessions with blood pressure varies, some studies have shown a positive association.